Homosexuality in Islam: Critical Reflection on Gay, Lesbian, and Transgender Muslims by Scott Siraj al-Haqq Kugle (Oxford: Oneworld, 2010. pbk 335 pages) (American Journal of Islam and Society, 2011)
Scott Siraj al-Haqq Kugle’s Homosexuality in Islam: Critical Reflectionon Gay, Lesbian, and Transgender Muslims is a comprehensive, engaging,and original rereading of the formative Islamic texts and traditions. Targetedat both academic and popular readers, the book has two prime objectives:to push heterosexual Muslims to confront their own prejudices abouthomosexuality within the Muslim community, and to give lesbian, gay, andtransgender Muslims greater confidence and the ability to speak about theirsexual realities in regard to the Islamic intellectual tradition ...